2007
DOI: 10.4049/jimmunol.179.7.4929
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Induced Cytidine Deaminase Expression in Follicular Dendritic Cell Networks and Interfollicular Large B Cells Supports Functionality of Ectopic Lymphoid Neogenesis in Autoimmune Sialoadenitis and MALT Lymphoma in Sjögren’s Syndrome

Abstract: Demonstration of ectopic germinal center-like structures (GC-LSs) in chronically inflamed tissues in patients with autoimmune disorders is a relatively common finding. However, to what extent ectopic lymphoid structures behave as true GC and are able to support class switch recombination (CSR) and somatic hypermutation (SHM) of the Ig genes is still debated. In addition, no information is available on whether CSR and SHM can take place in the absence of GCs at extrafollicular sites in an ectopic lymphoid tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 46 publications
(47 reference statements)
11
194
2
Order By: Relevance
“…Whether GL7 int B cells were located at an extrafollicular or follicular site in the PP is not known. In support of an interfollicular site for IgA CSR in PP, AID mRNA expression accompanied by switch a-CT has been found in secondary lymphoid organs outside the GC, scattered in the T cell zone and within the mantle zone (46)(47)(48). Nevertheless, in this study we provide compelling evidence that T cell-independent gut IgA CSR occurs in the PP at a stage before manifest GC formations and that such IgA cells carry largely unmutated V region sequences.…”
Section: Discussionsupporting
confidence: 63%
“…Whether GL7 int B cells were located at an extrafollicular or follicular site in the PP is not known. In support of an interfollicular site for IgA CSR in PP, AID mRNA expression accompanied by switch a-CT has been found in secondary lymphoid organs outside the GC, scattered in the T cell zone and within the mantle zone (46)(47)(48). Nevertheless, in this study we provide compelling evidence that T cell-independent gut IgA CSR occurs in the PP at a stage before manifest GC formations and that such IgA cells carry largely unmutated V region sequences.…”
Section: Discussionsupporting
confidence: 63%
“…Some of these ectopic lymphoid structures mirror classical germinal centers (GCs) [17,18]. This organization in lymphoid GC-like structures is well documented in pSS and can be detected in one-third of patients [19].…”
Section: Introductionmentioning
confidence: 81%
“…This sounds contradictory; however, Bombardieri et al 25 reported that neoplastic marginal zone-like B cells are AID-negative but have somatic and ongoing mutations. 26 On the other hand, Smit et al, 27 Pasqualucci et al 28 and Lossos et al 9 reported of lack of correlation between AID expression and intraclonal diversity of VH genes in B-cell non-Hodgkin's lymphomas.…”
Section: Duodenal Follicular Lymphomamentioning
confidence: 98%